The internationalization of nongovernmental organizations: Characteristics and challenges - Beatriz Gaspar; António Carrizo Moreira; Carolina Cercas; Rafaela Queirós; Salomé Campos (Administrative Sciences, 2022)
Although the internationalization of business firms has been intensively studied, the internationalization of nongovernmental organizations (NGOs) is still in a growing-up stage as NGOs are focused on serving specific social interests. They may not only be influenced by social, political, and economic goals, but also cater to social or humanitarian services dealing with health, environmental protection, and human rights. Based on the importance of NGOs and the lack of previous studies on their internationalization process, this paper analyzes the results of a systematic literature review (SLR) on the internationalization of NGOs. It is possible to conclude that this topic is under-researched and fragmented and has been dealt with by following qualitative studies. Moreover, the internationalization of NGOs is far from similar to the models that explain the internationalization of for-profit businesses. NGOs are clearly tuned to the services they provide and seek complementary resources from governmental sources and state agencies so that they are capable of providing a variety of human and financial resources. The main limitation of this study is that it is based solely on two academic databases: SCOPUS and WoS.
Keywords: 350; drivers; internationalization; NGOs; nongovernmental organizations; outcomes; SLR; social movements